2019
DOI: 10.3390/su11072043
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and Drivers for Improved Energy Efficiency in the Swedish Aluminium Industry and Aluminium Casting Foundries

Abstract: Industrial energy efficiency is important for reducing CO 2 emissions and could be a competitive advantage for companies because it can reduce costs. However, cost-effective energy efficiency measures are not always implemented because there are barriers inhibiting their implementation. Drivers for energy efficiency could provide means for overcoming these barriers. The aim of this article was to study the importance of different barriers to and drivers for improved energy efficiency in the Swedish aluminium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Haraldsson and Johansson [28] studied the importance of different barriers and drivers for improved energy efficiency in the Swedish aluminum industry. The data was collected through a questionnaire divided into different categories, covering 39 barriers and 48 drivers..…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Haraldsson and Johansson [28] studied the importance of different barriers and drivers for improved energy efficiency in the Swedish aluminum industry. The data was collected through a questionnaire divided into different categories, covering 39 barriers and 48 drivers..…”
Section: Literature Reviewmentioning
confidence: 99%
“…Figures 1 and 2 list the most relevant drivers and barriers for the implementation of EEMs as synthesized from three large-scale studies investigating the drivers and barriers in various organizations across Europe [8,9,11]. Comparable drivers and barriers can also be found at Haraldsson and Johansson [28] and Cagno et al [27]. Most of the drivers and barriers from the literature were also stated and confirmed by industry partners in the course of the case studies conducted for this research.…”
Section: Analysis Of Drivers and Barriersmentioning
confidence: 99%
“…However, the optimization of the operating parameters represents a no-cost strategy which can be implemented by SMEs to achieve real energy efficiency [31,32]. The various barriers encountered in increasing the SMEs' energy efficiency were investigated in [33][34][35][36]. Thus, six most important barriers were identified in [33] for the SMEs belonging to the ferrous material industry, namely, the government energy policy, the financial-economic problem, the managerial-organizational process, the technological factors, the quality of the workforce, the raw material, and the used fuel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, improving energy efficiency goes beyond the environmental dimension and Epstein and Yuthas [9] (p. 27) highlight becoming more energy efficient as an example of a sustainability choice that is a "no-brainer," due to its financial advantages. Potential cost reductions have also been identified as a top ranked driver for improving energy efficiency [10][11][12][13]. However, it has also been indicated that high initial investments and long payback periods hinder their adoption, e.g., [14,15], as well as lack of time and other priorities, e.g., [10,13,[15][16][17][18][19], and it has been posited that "in the absence of an explicit preference or dedicated budget for climate-change-or energy-related investments, companies tend to prefer investments that enable business growth" [20] (p. 422).…”
Section: Introductionmentioning
confidence: 99%